EFL OR ESL IN PAPUA: A NOT CLEAR-CUT ISSUE - Yohana Susana Yembise (Soegijapranata Catholic University, 2010)
The paper aims at analyzing situation in Papua in which English is taught as a Foreign Language and is about to be exercised as a Second Language in all schools. Papua is surrounded by 250 local languages and cultures in which Bahasa Indonesia is functioned as National Language. School students throughout Papua come from different socio-cultural background, the use of English as a Second Language will probably add another controversial issue in planning for education program in Papua. Education in Papua under Special Autonomy recommends English should be exercised as a Second Language in all forms of formal education. How could English is taught as a Second Language in such a multilinguallcultural situation where Indonesian is still being a barrier. The paper discusses critically issues regarding some conceptual frameworks of EFL and ongoing controversial issues as whether or not Papua is ready to exercise English as a Second Language in all schools throughout the province.